“WE HAVE CEASED TO BE A NATION IN RETREAT": REDEWENDUNGEN UND SPRICHWÖRTER IN MARGARET THATCHERS RHETORIK - Gläser, Rosemarie (Proverbium - Yearbook, 2014)
The article sets out to examine Margaret Thatcher’s rhetoric and individual style in her two autobiographies, The Downing Street Years (1993) and The Path to Power (1995) in the light of paroemiology and phraseology. The linguistic analysis is focused on fixed expressions (i.e. phraseological units) in the function of words (i.e. nominations) and sentences (as propositions), with special reference to proverbial and metaphorical sayings; quotations and winged words; maxims and slogans. These set expressions constitute a salient feature of Margaret Thatcher’s rhetoric in her memoirs. Another remarkable quality is her open-minded account of the process of speech-writing for her public performances – in close cooperation with journalists, ministers and specialists in many subject areas. The final version of a speech always included meticulous work on words and phrases, the structuring of the whole text, but also on the prosody for presentation, done by the speaker herself.